Love them all: mothers provide care to foreign eggs in the European earwig Forficula auricularia. (9th February 2019) - Van Meyel, Sophie; Devers, Séverine; Meunier, Joël
Abstract: The rejection of foreign individuals is considered a central parameter in the evolution of social life. Within family units, parents are typically thought to reject foreign offspring to ensure that their investment into care is directed towards their own descendants. Whereas selection for such kin bias is expected to be high when parental care is extended and involves numerous and energetically costly behaviors, it can be reduced when the acceptance of foreigners provide subsequent benefits to offspring and when alternative parental strategies limit the risk of clutch parasitism. In this study, we investigated the outcome of these conflicting selection pressures in the European earwig. Our results overall demonstrate that mothers do not eliminate foreign eggs, provide the same level of care to both foreign and own eggs (egg grooming, egg defense, and maternal return) and pay the same costs of care in terms of weight loss and immunity when tending each type of eggs. We also show that foreign and own eggs exhibit similar development time, hatching success and lead to comparable juvenile quality. Interestingly, our results reveal that tending eggs (of any origin) reduces mothers' weight loss during this long period, possibly due to egg cannibalism. Hence, these findings emphasize the difficulty to predict the occurrence of kin bias, and stress the need to broaden our knowledge on the net benefits of egg rejection for parents to better understand the general importance of kin bias in the evolution of pre-hatching parental care. Abstract : Although rejecting unrelated conspecifics is considered a key parameter in social evolution, we show that family-living earwig does not. We demonstrate that earwig mothers accept and provide extensive care to foreign eggs just as they do to their own eggs. This suggests that the risks and/or the costs of misdirected egg care are limited in this species, and raise questions on the general importance of kin bias in the evolution of parental care.